PENGARUH KENAIKAN UPAH MINIMUM REGIONAL (UMR) DAN JUMLAH PENDUDUK TERHADAP PENERIMAAN PAJAK BUMI DAN BANGUNAN (PBB) - Heru Pranoto, Sarastanto Aulia; Handayani, Dewi Sri; Fandil, Fandil (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of the increase in the Regional Minimum Wage (UMR) and the number of residents on the revenue of Land and Building Tax (PBB) in South Semarang District, Semarang City in 2021–2023. This study uses a quantitative method with a descriptive approach and multiple linear regression analysis. Primary data were obtained by distributing questionnaires to 100 respondents, which were determined by random sampling techniques based on the Slovin formula. The results of the analysis show that UMR has a positive and significant effect on PBB revenue with a significance value of <0.05. Meanwhile, the number of residents does not have a significant partial effect on PBB revenue. However, simultaneously UMR and population have a significant effect on PBB revenue in South Semarang District. The coefficient of determination (Adjusted R²) shows that the independent variables are able to explain the variation in PBB revenue by a fairly high percentage. Based on these findings, it is recommended that local governments consider the dynamics of UMR in policies to increase regional tax revenue and pay attention to population growth patterns as supporting factors in the long term.